Publications on the History of Cities and Their Bibliography (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
This article analyzes the inclusion of literature on urban development, economy, culture, science, art, historical topography in the sections of the bibliographic guide on the history of ancient cities in Uzbekistan. The importance of creating a bibliography of literature on the history of urban planning of a specific city from ancient times to the present has been revealed to all readers.